The value of the variable y is ![y=6](https://tex.z-dn.net/?f=y%3D6)
Explanation:
The given equation is ![\frac{6}{y-4}-\frac{y}{y+2}=\left(\frac{6}{y-4}\right)\left(\frac{y}{y+2}\right)](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7By-4%7D-%5Cfrac%7By%7D%7By%2B2%7D%3D%5Cleft%28%5Cfrac%7B6%7D%7By-4%7D%5Cright%29%5Cleft%28%5Cfrac%7By%7D%7By%2B2%7D%5Cright%29)
Taking LCM on LHS of the equation, we get,
![\frac{6(y+2)-y(y-4)}{(y-4)(y+2)}=\left(\frac{6}{y-4}\right)\left(\frac{y}{y+2}\right)](https://tex.z-dn.net/?f=%5Cfrac%7B6%28y%2B2%29-y%28y-4%29%7D%7B%28y-4%29%28y%2B2%29%7D%3D%5Cleft%28%5Cfrac%7B6%7D%7By-4%7D%5Cright%29%5Cleft%28%5Cfrac%7By%7D%7By%2B2%7D%5Cright%29)
Simplifying the term on RHS of the equation, we get,
![\frac{6(y+2)-y(y-4)}{(y-4)(y+2)}=\frac{6 y}{(y-4)(y+2)}](https://tex.z-dn.net/?f=%5Cfrac%7B6%28y%2B2%29-y%28y-4%29%7D%7B%28y-4%29%28y%2B2%29%7D%3D%5Cfrac%7B6%20y%7D%7B%28y-4%29%28y%2B2%29%7D)
Since, both the sides of the equation have the same denominator, we can cancel them.
Thus, we have,
![6(y+2)-y(y-4)=6 y](https://tex.z-dn.net/?f=6%28y%2B2%29-y%28y-4%29%3D6%20y)
Multiplying the terms within the bracket, we get,
![6y+12-y^2-4y=6 y](https://tex.z-dn.net/?f=6y%2B12-y%5E2-4y%3D6%20y)
Adding the like terms, we have,
![2y+12-y^2=6 y](https://tex.z-dn.net/?f=2y%2B12-y%5E2%3D6%20y)
Subtracting both sides by
, we have,
![-4y+12-y^2=0](https://tex.z-dn.net/?f=-4y%2B12-y%5E2%3D0)
Factoring the equation, we get,
![(y+2)(y-6)=0](https://tex.z-dn.net/?f=%28y%2B2%29%28y-6%29%3D0)
![y=-2, y=6](https://tex.z-dn.net/?f=y%3D-2%2C%20y%3D6)
The values of the variable y are ![y=-2, y=6](https://tex.z-dn.net/?f=y%3D-2%2C%20y%3D6)
At the point
, the equation
becomes undefined.
Thus, the value of the variable y is ![y=6](https://tex.z-dn.net/?f=y%3D6)